Instructional media resources improvisation by teachers for effective instructional delivery in public secondary schools in Nigeria (2018)
Instructional media resources are very important for effective teaching in the public secondary schools in Nigeria. The print, non-print and electronic media resources serve different purposes in disseminating educational information to the students through the teachers. It is a pity that many of these instructional media resources were not provided for in the public secondary schools especially the state-owned secondary schools are not well equipped with necessary instructional media resources by the government as a result of this, teachers were not utilizing or inadequately utilizing the instructional media resources for teaching. This situation makes teaching passive and unproductive leading to poor product participation in teaching-learning activities and poor retention of learning leading to poor academic performance. It is then recommended that teachers should improvised for available instructional media resources with local materials in their environments apart from this, they should publish books to the library every session, collaborate with students in improvising instructional media resources such as chat, model, scarce apparatus among others. All these could be done through the learning of skills in media improvisation.